Public Administration Innovation in The Integration of Waste Management and Urban Farming: A Study of The "Tanami Tanata" Movement - Ansar Amir; Mardihang Haruna (Interdisciplinary Social Studies, 2025)
The Tanami Tanata Movement in Makassar City is a public administration innovation that integrates organic waste management with urban farming practices. This study uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The results of the study show that this movement is able to significantly reduce the generation of organic waste while strengthening family food security. Public administration innovations can be seen through multi-actor collaboration, participatory governance platforms, the implementation of local circular economy, and the digitization of services through the "Sampah Tukar Sayur" program. The integration of waste management with urban farming results in a sustainable cycle from waste to productive resources, which provides ecological, social, and economic benefits. In addition, this program encourages the birth of micro businesses based on urban agriculture and increases public awareness of the principle of zero waste. This study emphasizes the importance of collaboration-based public administration innovation in addressing urban challenges while supporting the achievement of sustainable development goals.